Social media indicate loneliness among teenagers / Nur Syafura Mohd Yusof...[et al.] - Mohd Yusof, Nur Syafura; Mohd Syafiq, Sarah Nur Syifa; Shameen, Muhammad Aimran; Anuar, Aina; Dino Affendi, Aimi Izyan; Fauzi, Hariz (Faculty of Communication & Media Studies, 2020)
Loneliness is not something all of us want to have but some of us can't escaped from that feeling. The feeling itself comes within yourself and need to be controlled if not it will lead to mental health problem. One of the reason teenagers (millennials) nowadays could feel lonely is because the amount of time they spend on their phone scrolling thru social media. This study use in-depth interview to get to know why the millennials spend more time on their phone rather than doing activities than need to be communicate face-to-face. Qualitative results show's that, social media are easy to access on the go with portable internet everywhere which majority of them have each one.